2007
DOI: 10.1111/j.1559-4564.2007.06530.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Metabolic Syndrome in Hypertensive Patients: Results From the ICEBERG Study

Abstract: The Intensive/Initial Cardiovascular Examination Regarding Blood Pressure Levels: Evaluation of Risk Groups (ICEBERG) study was aimed at evaluating the components of the metabolic syndrome (MS) for cardiovascular risk stratification in hypertensive patients. The ICEBERG study consisted of 2 subprotocols: ICEBERG-1, conducted at 20 university hospitals, and ICEBERG-2, conducted at 197 primary health care centers. Each subprotocol had 2 patient profiles: patients diagnosed with hypertension and receiving medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The exercise level in this population can also be assumed to be more than that of the general population. In this aspect, despite a potentially different life style compared to whole Turkish population, the HDL-c was not substantially different from the recent epidemiologic studies even the ones evaluating the individuals with high cardiovascular risk (21)(22)(23)(24). Secondly, exclusion of 4 patients with coronary artery disease from the analyses might have contributed the relatively high levels of HDL-c, though the small number of these participants is unlikely to influence the results.…”
Section: Study Limitationsmentioning
confidence: 56%
See 2 more Smart Citations
“…The exercise level in this population can also be assumed to be more than that of the general population. In this aspect, despite a potentially different life style compared to whole Turkish population, the HDL-c was not substantially different from the recent epidemiologic studies even the ones evaluating the individuals with high cardiovascular risk (21)(22)(23)(24). Secondly, exclusion of 4 patients with coronary artery disease from the analyses might have contributed the relatively high levels of HDL-c, though the small number of these participants is unlikely to influence the results.…”
Section: Study Limitationsmentioning
confidence: 56%
“…Similarly, Mahley et al (26) showed that HDL-c in prepubertal Turkish children was not low compared to that in children of similar age group in different countries, another finding supporting the idea that HDL-c is not "genetically" low in Turkish population. As summarized previously, recent epidemiologic studies showed that HDL-c was not as low as TEKHARF and Turkish Heart Study stated (21)(22)(23)(24). It is difficult to conclude the reason(s) of the low HDL-c in TEKHARF and Turkish Heart Study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thirdly, tbe main focus of our study was that, altbough Turkish population was regarded as a population with characteristically low HDL-C in relatively old studies (2, 3), we don't tbink so according to tbe recent epidemiologic studies including ours (4)(5)(6). In addition, wbat we observe in our daily clinical practice is HDL-C cbanges little and stays witbin a narrow band during follow-up of the patients.…”
Section: Author S Replymentioning
confidence: 86%
“…There are some studies in which 24-hour urinary sodium excretion was followed during salt restriction (3,4). On the contrary, some investigators did not follow 24-hour urinary sodium excretion (2,5). Surely, it would be better to restrict salt followed by urinary sodium excretion.…”
mentioning
confidence: 99%